دراسة مقارنة بعض التراكيب الكيميائية لنوعي الكمأة البيضاء Tuber tirmania والسوداء Tuber melanosporun - عبود فواز; روهم قرياقس (Latakia University Journal -Biological Sciences Series, 2019)
أجري البحث في مخابر كلية الزراعة بدير الزور عام2005-2006م حيث درس التركيب الكيميائي لنوعي الكمأة البيضاء والسوداء ( رطوبة، دسم، بروتين، أملاح معدنية ،السكريات الكلية، فيتامين c ) وأظهرت نتائج التحليل الكيميائي أن الكمأة البيضاء تفوقت على السوداء بمقدار ما تحتويه من فيتامين c بمعدل 5 أضعاف أما بنسبة الرطوبة والسكريات الكلية والبروتين فكانت النسبة متقاربة في نوعي الكمأة. وبنسبة الدسم تفوقت الكمأة السوداء على البيضاء بمقدار الضعف أما بالنسبة للأملاح المعدنية فتفوقت الكمأة السوداء على البيضاء بمقدار ما تحتويه من عناصر Mn ،Fe،Cu. This research was carried out in the laboratories of the 2nd Faculty of Agriculture in Der.Ezor in the year 2005-2006. In this study, the chemical structure of tuber tirmania and tuber melanosporun was investigated (moisture, fat, protein, menirals, Total sugars and vitamin – c - ). The results of the chemical analysis showed that tuber tirmania was five times richer in vitamin - c - than tuber melano sporun .As for moisture, total sugars and protein, the percentage was almost the same. But for fat, the tuber melano sporun had more fat (at the time ) than the tuber tirmania . As for the minerals, tuber melano sporun again surpassed the tuber tirmania in elements such as Cu , Fe and Mn .